Bare spot and tubercle of Assaki - Alashkham, Abduelmenem (JSES Open Access, 2017)
BACKGROUND: The definition of the bare spot and tubercle of Assaki is controversial, with studies reporting different incidences, locations, and clinical significance. The aims of this study were to evaluate the incidence of the bare spot, to determine the length and width of the bare spot, and to assess the relationship between the bare spot and tubercle of Assaki. MATERIALS AND METHODS: A total of 140 shoulders from 30 men and 40 women were dissected and examined. After exposure of the glenoid fossa with the glenoid labrum attached, direct measurement of the length and width of the bare spot was undertaken using digital calipers. The repeatability and reliability of the measurements was assessed using Kruskal-Wallis one way analysis of variance on ranks, with statistical significance set at P < .05. RESULTS: A bare spot was observed in 80.7% (n = 113) of shoulders, being more common in men than in women, with an overall mean length and width of 7.2 mm and 6.2 mm. It was significantly longer (P = .002) and wider (P = .018) in men. CONCLUSION: A bare spot exists within the glenoid fossa and differs from the tubercle of Assaki. It is a characteristic round to oval lesion in the central or eccentric cartilage. It should not be misdiagnosed as a pathologic lesion.